Research of measurements errors of geometrical parameters of the phytoplankton - Безвесільна, Олена Миколаївна; Войцицький, Анатолій Павлович; Єльнікова, Тетяна Олександрівна (Eastern-European Journal of Enterprise Technologies, 2009)
The experimental research of measurements errors of geometrical parametres of the phytoplankton is spent. It is checked up probability of mathematical models of these errors and results of calculation accuracy characteristics of the automated system for measurements of geometrical parametres of a phytoplankton are confirmed. The received results can be used for working out of the automated information-measuring systems and their use in the industry